Workshop Pembuatan Pangan Sehat dengan Teknologi Kimia Sederhana di GBI Bukit Zaitun Medan - Alexander, Irving Josafat (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
Public health is strongly influenced by daily dietary habits. Field observations indicate a low level of community understanding regarding healthy food and limited skills in safely and nutritiously processing ingredients. The Healthy Food Production Workshop Using Simple Chemical Technology at GBI Bukit Zaitun Medan was conducted to address this need, aiming to improve participants’ knowledge, skills, and awareness related to healthy food. The method used was a community service approach with a participatory-educational design based on learning by doing. The workshop was conducted in three sessions: a theoretical presentation on healthy food and simple chemical technology, hands-on practice in preparing healthy food using local ingredients and simple tools, and a reflective discussion to evaluate participants’ learning experiences. Data were collected through observation, brief interviews, pre- and post-workshop questionnaires, and field documentation. Analysis was performed descriptively, both qualitatively and with simple quantitative measures, to assess changes in participants’ knowledge, skills, and attitudes. The results showed an increase in participants’ understanding from 35% in the pre-test to 85% in the post-test, as well as practical competence in producing healthy food products, including probiotic drinks, steamed low-oil foods, and natural preservation using spices. Furthermore, most participants demonstrated strong motivation to change their dietary habits and apply the skills learned at home. This workshop demonstrates the effectiveness of a community-based approach in enhancing healthy food literacy and practical skills, providing a foundation for the development of sustainable programs that support healthy living within local communities.